2012
DOI: 10.1016/j.gaceta.2011.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Guías de práctica clínica y atención primaria. Informe SESPAS 2012

Abstract: Clinical practice guidelines are intended to serve as a bridge between the decision levels and the sources of knowledge, giving decision makers the best synthesis of scientific evidence and an analysis of context, to provide elements of judgement and to transfer scientific knowledge into clinical practice. However, the actual impact on health care is variable and effectiveness in changing medical practice, moderate. Qualitative and quantitative studies show that most primary care physicians consider that the g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
2
0
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 15 publications
2
2
0
3
Order By: Relevance
“…The frequency of consulting CPGs is probably conditioned by the lack of time in the office. In our findings and in the previous literature [21,38,39] the latter was already indicated as the main barrier to using CPGs. On the contrary, the readiness by younger doctors to use CPGs could be explained by their training in the principles of evidence-based medicine and by their higher awareness of this type of tools.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…The frequency of consulting CPGs is probably conditioned by the lack of time in the office. In our findings and in the previous literature [21,38,39] the latter was already indicated as the main barrier to using CPGs. On the contrary, the readiness by younger doctors to use CPGs could be explained by their training in the principles of evidence-based medicine and by their higher awareness of this type of tools.…”
Section: Discussionsupporting
confidence: 78%
“…In our study, lack of time to access the CPGs is the main reported barrier to their use, in both levels of care. It is difficult to tell whether this assertion is based on task overload or on the fact that consultation of CPGs is not a priority in doctors' daily activity; however, it is reflected in the previous literature . These results reinforce the findings from the previous qualitative study carried out as part of the project, where the participating doctors suggested the need of a brief, easily accessible CPG format.…”
Section: Discussionsupporting
confidence: 71%
“…Las guías de práctica clínica (GPC) podrían tener un importante papel en la mejora de los aspectos previamente mencionados, si bien su implementación conlleva importantes dificultades 13,14 . Una de las propuestas para conseguir superar estas barreras es su incorporación en el flujo de trabajo 15,16 y su integración con los registros clínicos electrónicos 17 mediante el desarrollo de sistemas de apoyo a las decisiones clínicas (SADC), definidos como «herramientas diseñadas para apoyar las decisiones clínicas, en las que se generan recomendaciones según las características de los pacientes» 18 .…”
Section: Introductionunclassified
“…5 As regards care, there is evidence of an unsupported variability in the diagnosis and treatment, both by defect 6---10 and excess. 13,14 One of the proposals to overcome these barriers is to include it in the workflow 15,16 and to integrate it with electronic clinical records 17 through the development of clinical decision support systems (CDSS), defined as ''tools designed for the support of clinical decisions, where recommendations are made according to the characteristics of the patients''. 13,14 One of the proposals to overcome these barriers is to include it in the workflow 15,16 and to integrate it with electronic clinical records 17 through the development of clinical decision support systems (CDSS), defined as ''tools designed for the support of clinical decisions, where recommendations are made according to the characteristics of the patients''.…”
Section: Introductionmentioning
confidence: 99%